Fishermen's Strategies in Dealing with Globalization - Sartika Khairani Siregar; Rudiyanto Rudiyanto; Bayu Asih Yulianto; Pujo Widodo; Herlina Juni Risma Saragih (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
The era of globalization has a positive and negative impact on human life, including fishermen. The positive impact that people can obtain consumptive goods more easily, the number of jobs, the development of skills and skills, and advanced technology. This can also be seen in the maritime sector and encourages the acceleration of the pace of the economy. The negative impact of globalization is many business competitors, low education which is the cause of low welfare, especially on the lives of coastal communities. For this reason, this research uses qualitative research methods with a descriptive approach. The result of this study is that it is necessary to use asset improvement in fishermen by utilizing stakeholders from the government such as the implementation of HDI (Human Development Index) and modernization of fishing gear.